Overview and evaluation of the Indonesia's water resources management policies for food security - Andi Setyo Pambudi (Indonesian Journal of Applied Environmental Studies, 2021)
Water and water resources must be maintained by their functions and benefits to meet the needs of all sectors and future generations. One important part of sustainable water resource management that is of considerable interest to the government is irrigation which aims to achieve food security. Food security in Indonesia Development in the field of food security and poverty alleviation in rural areas is one of the leading sectors in the nine national development priority agendas contained in “Nawa Cita”. The development of food security in Indonesia faces many complex problems, such as irrigation infrastructures maintenance, regulations, land use change, population, policy implementation, coordination among stakeholders and also budget issues. The method in this study is a qualitative method through the literature review related to the management of water resources for food security in Indonesia. This paper seeks to evaluate the development irrigation policies as part of sustainable water management that supports food security in Indonesia. Literature sources are 5 main regulations, 5 papers and some government reports. To support increased food security, the direction of the Indonesian Government's policy in strengthening food security from the irrigated agricultural sector is realized through a strategy to increase production capacity and improve irrigation network services. The problem of the availability of irrigation water must be addressed quickly by upstream conservation, maximizing capacity through normalization of existing reservoirs, and continuing to build dams to have water storage containers that can accommodate planting season throughout planting. Air dan sumber daya air harus dijaga fungsi dan manfaatnya untuk memenuhi kebutuhan semua sektor dan generasi mendatang. Salah satu bagian penting dari pengelolaan sumber daya air berkelanjutan yang cukup menarik perhatian pemerintah adalah irigasi yang bertujuan untuk mencapai ketahanan pangan. Di Indonesia, pembangunan di bidang ketahanan pangan dan pengentasan kemiskinan di pedesaan merupakan salah satu sektor unggulan dalam sembilan agenda prioritas pembangunan nasional yang tertuang dalam “Nawa Cita”. Pembangunan ketahanan pangan di Indonesia menghadapi banyak masalah yang kompleks, seperti pemeliharaan infrastruktur irigasi, regulasi, perubahan penggunaan lahan, kependudukan, implementasi kebijakan, koordinasi antar pemangku kepentingan dan juga masalah anggaran. Metode dalam penelitian ini adalah metode kualitatif melalui studi pustaka terkait pengelolaan sumber daya air untuk ketahanan pangan di Indonesia. Tulisan ini berupaya mengevaluasi kebijakan pembangunan irigasi sebagai bagian dari pengelolaan air berkelanjutan yang mendukung ketahanan pangan di Indonesia. Sumber literatur adalah lima peraturan utama, lima makalah dan beberapa laporan pemerintah. Untuk mendukung peningkatan ketahanan pangan, arah kebijakan Pemerintah Indonesia dalam memperkuat ketahanan pangan dari sektor pertanian beririgasi diwujudkan melalui strategi peningkatan kapasitas produksi dan peningkatan pelayanan jaringan irigasi. Masalah ketersediaan air irigasi harus segera diatasi dengan konservasi di wilayah hulu, memaksimalkan kapasitas melalui normalisasi waduk yang ada, dan terus membangun bendungan untuk memiliki wadah penampung air yang dapat mencukupi kebutuhan pasokan sepanjang musim tanam.